Analysis of compression in uniform and non-uniform GDL microstructures on water transport. Issue 13 (21st October 2022) - Anyanwu, Ikechukwu S.; Niu, Zhiqiang; Jin, Shaohui; Jiao, Kui; Gong, Zhengwei; Liu, Zhi
ABSTRACT: A 3D compressed gas diffusion layer (GDL) microstructure is developed based on the finite volume method (FVM) and used to evaluate water transport behavior. The compressed GDL microstructure and two-phase flow VOF model are developed and validated on the OpenFOAM CFD platform. The models are compared to experimental data, with good agreement. Consequently, the reconstructed GDL microstructures are subjected to compressive stresses. The water uptake behavior in the compressed samples with different (CR) compression ratios (10% CR, 20% CR, and 40% CR) is compared to that in an uncompressed GDL microstructure. Also, the effects of GDL wettability, water pressure, and non-uniform fiber diameter arrangement in GDLs are investigated. In GDL microstructures, two-phase interaction is influenced by the GDL contact angle, compression ratio, water inlet pressure and capillary pressure. It is found that excessive compression on GDLs constricts the pores, thereby restricting access of water through the pores. As such, 10% CR was found to be the safe limit with just 8% saturation drop. On the other hand, altering the fiber structural arrangement through unequal-sized fiber diameter had very little impact on water saturation in the through-plane direction of both the uncompressed and compressed GDL microstructures. As such, the excessive introduction of the unequal-sized fibers may not be the right choice, especially under compressive forces. Thus care must be taken in the treatment of GDL carbon papers and clamping force during assembly since these significantly influences water patterns in them.